Kajian Karakteristik Fisik dan Mekanik Edible Film Berbasis Pati Umbi Suweg (Amorphophallus paeoniifolius) dengan Variasi Konsentrasi Lilin Lebah - Evi Lusiana Dwi Safitri; Warkoyo Warkoyo; Rista Anggriani (Universitas Muhammadiyah Malang, 2020)
Suweg tuber contains very high starch so that it can be used as one of the ingredients for the edible film. The use of a single ingredient from the starch group has a disadvantage because it has a weak and rigid, so it needs to be added ingredients to improve the nature of the edible film, namely by adding beeswax. The addition of beeswax is expected to improve the physical and mechanical properties of the edible film because its hydrophobic nature is a barrier to the loss of steam from products packed by the edible film. This research used a factorial randomized block design using two factors: suweg tuber starch concentration (3%.4%, and 5%) and beeswax concentration (1%.2%, and 3%). Parameters of research included analysis of raw materials in the form of water content, starch content and amylose starch content of suweg tubers whileanalysis edible film included the thickness, transparency, tensile strength, elongation, solubility, water vapor transmission rate and surface structure. The results showed that there was a very real interaction between the addition of suweg tuber and beeswax starch to thickness, elongation, tensile strength, and water vapor transmission rate and there was a real interaction with the transparency and solubility of edible film. The best treatment with near-standard results is edible film with suweg tuber starch concentration 3% (b/ v) and beeswax concentration 1% (b/ v) The surface structure of edible film on starch addition 3% (b/ v) results in a structure that more flat and soft, while the addition of beeswax 1% (b/ v) results in smaller pores.